Interactive promotional design for zoo Melaka - Lau, Wai Sin (Universiti Malaysia Sarawak (UNIMAS), 2014)
Technology has been a part of our daily life. This interactive design is an initiative new branding for Zoo Melaka. Researcher will focus on the product development process based on virutal prototyping, which allows earlier evaluation of product performance from the users. Through the multi-platform usability testing, the impact integration of visual study and UX (user experience) is given new experience for visitors as well as awareness of the environment and animals.